Exploring the role of identity in pro-environmental behavior: cultural and educational influences on younger generations - Wild, Steffen; Schulze Heuling, Lydia (Frontiers in Psychology, 2024)
It is of paramount importance to gain an understanding of pro-environmental behaviour if we are to successfully address the climate crisis. The existing body of research provides evidence that identity influences pro-environmental behaviour. However, such research is often too generalised, and researchers are challenged to conduct robust analysis with regard to the specific cultural and educational backgrounds of the next generation. The present study aims to ascertain whether personal or social identity exerts a more pronounced effect on three distinct dimensions of pro-environmental behaviour, employing the tenets of self-categorisation theory. The data was collected in a cross-sectional survey with a total of 568 cooperative students from academic disciplines in engineering and economics. The reliability of the scales is satisfactory (ω = .76–.88), and the hypotheses are tested by estimating structural equation models. Our research demonstrates that while social identity exerts a stronger influence on activist behaviour than personal identity, personal identity has a more pronounced effect on consumer behaviour than social identity. Nevertheless, no general statement can be made regarding the relative strength of the effects of personal and social identity on pro-environmental behaviour dimensions.